PENGARUH MOTIVASI PADA MINAT SARJANA AKUNTANSI UNIVERSITAS UDAYANA UNTUK MENGIKUTI PPAK - Vesperalis, A.A Ayu Dewi; Muliartha RM, Ketut (E-Jurnal Akuntansi, 2017)
This study aimed to examine the effect of motivation on interest Udayana University undergraduate accounting for follow PPAk. This research was conducted at the Faculty of Economics and Business, University of Udayana in accounting undergraduate class of 2015. Sampling method is non probability sampling with purposive sampling technique. Data were collected using survey method with questionnaire technique. Respondents of this study were 167 people. Data analysis model used is multiple linear regression. Results of the analysis proved that social motivation variable does not affect the interests of Udayana University undergraduate accounting to follow the Accounting Profession. While variable career motivation, economic motivation and motivation of seeking an undergraduate accounting effect on the interests of Udayana University undergraduate accountingto follow the Accounting Profession Education (PPAk).
Keywords: Social Motivation, Motivation Career, Economic Motivation, Motivation Degree,Following interest PPAk